Evaluation of agro-morphological and molecular characters of 22 rice landraces of East Timor - LUIS MANUEL BRANCO; ENDAH RETNO PALUPI; SATRIYAS ILYAS; BAMBANG SAPTA PURWOKO; AGUS PURWITO (Society for Indonesian Biodiversity, 2023)
Abstract. Branco LM, Palupi ER, Ilyas S, Purwoko BS, Purwito A. 2023. Evaluation of agro-morphological and molecular characters of 22 rice landraces of East Timor. Biodiversitas 24: 2536-2546. Landraces play an important role in the local food security and sustainable development of agriculture as a source of genes that control important traits adaptive to environmental conditions. The study aimed to characterize the agro-morphological and molecular characteristics of 22 rice landraces of East Timor (Timor Leste). The research was conducted in April-August 2018 in Caibada-Baucau-East Timor. Soil analysis was conducted at the Soil Laboratory of the Agronomy and Horticulture Department, IPB University. Materials used were 22 rice landraces seeds and one check variety. The seeds were germinated in seedbed seedlings with a basin (30 cm x 25 cm). The seedlings were planted in the field 16 days after sowing in a plot of 1.5 m x 7.0 m and a spacing of 25 cm x 25 cm, with an isolation distance between plots of ±3 m. Data collection was based on nine growth phases of rice. The cluster analysis based on agro-morphological characters resulted in 6 groups with a similarity coefficient of 0.17 or 17%, showing a high level of diversity. The lowest yield was Ale Kukefuhu (290 g/m2), and the highest was Hare Nona Portu (979 g/m2). Using 10 RAPD markers, the 22 rice landraces samples produced 77 DNA fragment bands with sizes between 300 bp-1475 bp, averaging 3.35 alleles per landrace; polymorphic rates of 8.1. OPA8, OPH1, and OPH7 markers were the highest (100.00%), and OPF5 was the lowest (66.67%) polymorphic percentage. Based on the molecular marker, the coefficient of similarity of the landraces ranged from 0.12 to 0.51, and they were grouped into five clusters.